Political change in underdeveloped countries : nationalism & communism / edited by John H Kautsky - "Kautsky, John H.(ed.)" (New York, 1962)
This book was conceived to answer the need for a general introduction to the politics of underdeveloped countries. It consists of an extended essay by the editor, a political scientist, and twelve articles by the contributors from several of social sciences.
Keywords: Political Science